Observation of Parity-Time Symmetry in Optically Induced Atomic Lattices - Zhang, Zhaoyang; Zhang, Yiqi; Sheng, Jiteng; Yang, Liu; Miri, Mohammad-Ali; Christodoulides, Demetrios N; He, Bing; Zhang, Yanpeng; Xiao, Min (Physical review letters, 2016)
We experimentally demonstrate PT-symmetric optical lattices with periodical gain and loss profiles in a coherently prepared four-level N-type atomic system. By appropriately tuning the pertinent atomic parameters, the onset of PT-symmetry breaking is observed through measuring an abrupt phase-shift jump between adjacent gain and loss waveguides. The experimental realization of such a readily reconfigurable and effectively controllable PT-symmetric waveguide array structure sets a new stage for further exploiting and better understanding the peculiar physical properties of these non-Hermitian systems in atomic settings.